Improving Fifth-Grade Students’ Learning Outcomes in Social Studies through the Inquiry Method at SDN 1 Kalora - Silky Mayastika; Rizal Rizal; Dyah Aini Purbarani; Yun Ratna Lagandesa (Journal of Educational Sciences, 2026)
This study aimed to improve the learning outcomes of fifth-grade students in Social Studies through the implementation of the inquiry learning method at SDN 1 Kalora. The research identified that the low student performance was caused by the dominance of the lecture method, limiting student participation. A Classroom Action Research (CAR) design was employed across two cycles, involving 16 students from SDN 1 Kalora in the 2025/2026 academic year. The data were collected through observations of both teacher and student activities and learning outcome tests, analyzed using descriptive quantitative and qualitative methods. Results showed that the inquiry learning method led to improvements in both student activity and learning outcomes. The average student score increased from 60.31 with a mastery level of 50% in Cycle I to 68.12 with a mastery level of 75% in Cycle II. Student activity rose from 67.85% to 92.89%, and teacher activity improved from 73.80% to 95.23%. This study concludes that the inquiry learning method effectively enhances student engagement and learning outcomes in Social Studies at SDN 1 Kalora.